Association of longer telomere length in cancer cells and cancer-associated fibroblasts with worse prognosis. (26th December 2022) - Matsuda, Yoko; Ye, Juanjuan; Yamakawa, Keiko; Mukai, Yuri; Azuma, Kazuki; Wu, Linxuan; Masutomi, Kenkichi; Yamashita, Taro; Daigo, Yataro; Miyagi, Yohei; Yokose, Tomoyuki; Oshima, Takashi; et al.
Abstract: Background: Telomere dysfunction has been reported to be directly involved in carcinogenesis owing to chromosomal instability and immortalization; however, the clinicopathological significance of telomeres remains controversial. We have shown that telomere shortening occurs in normal-appearing duct cells at initiation and then continues during the progression of pancreatic cancer. In this study, we determined the clinicopathological and prognostic value of telomere length (TL) in cancer progression. Methods: TL in both cancer cells and cancer-associated fibroblasts (CAFs) was analyzed by high-throughput quantitative fluorescence in situ hybridization using a previously reported cohort comprising 1434 cases of adenocarcinoma (ADC), squamous cell carcinoma (SCC), adenosquamous carcinoma, hepatocellular carcinoma, and renal cell carcinoma (RCC), which are known cancers with a statistically significantly low incidence of alternative lengthening of telomeres. Cases were divided into 2 groups as follows: longer and shorter telomeres, according to the median TL of cancer cells and CAFs. The statistical significance of TL in cancer cells and CAFs on clinicopathological characteristics and prognosis was analyzed. Results: There was a close association between TL in cancer cells and CAFs. Longer telomeres in cancer cells and CAFs were associated with aggressive features such as advanced stage, high mitosis score and nuclear score, poorly differentiated cancer, and desmoplastic stroma in ADC. Furthermore, a longer TL was an independent prognostic factor for ADC, SCC, and RCC. Conclusions: Longer telomeres are associated with worse prognosis in ADC, SCC, and RCC. Thus, TL is a novel biomarker for the diagnosis of aggressive cancers with poor prognoses.